(untitled) (Journal of Engineering, 2012)
In this study, dead and live anaerobic biomass was used in biosorption of Pb(II), Cr(III) and Cd(II) ions from a synthetic wastewater. The biosorption was investigated by batch adsorption experiments. It was found that, the biosorption capacities were significantly affected by biosorbent dosage. The process follows Langmuir isotherm (regression coefficient 0.995, 0.99 and 0.987 for Pb(II), Cr(III) and Cd(II) ions, respectively, onto dead anaerobic biomass) model with uniform distribution over the biomass surface. The experimental uptake capacity was 51.56, 29.2 and 28 mg/g for Pb(II), Cr(III) and Cd(II), respectively, onto dead anaerobic biomass, compared with 35, 13.6 and 11.8 mg/g for Pb(II), Cr(III) and Cd(II), respectively, onto live anaerobic biomass. The percentage reductions of live compared with dead anaerobic biomass in uptake capacity were 32.3, 53.4 and 57.8 for Pb(II), Cr(III) and Cd(II), respectively. The results indicated that, the dead anaerobic biomass is suitable as an efficient biosorbent for the removal of Pb(II), Cr(III) and Cd(II) ions from wastewater.